Database and expert systems applications. 27th International Conference, DEXA 2016, Porto, Portugal, September 5-8, 2016, Proceedings /: 27th International Conference, DEXA 2016, Porto, Portugal, September 5-8, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available